2021
DOI: 10.3988/jcn.2021.17.2.164
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Endothelial Dysfunction in the Pathophysiology and Cerebrovascular Effects of Migraine: A Narrative Review

Abstract: Background and Purpose Migraine is a complex neurovascular disorder whose triggers are not entirely understood. Endothelial dysfunction might play a role in migraine, and there have been numerous reports on endothelium dysfunction and migraine pathophysiology, but their reciprocal cause–effect relationship remains unclear. This review reports the current evidence on endothelium dysfunction, its link with migraine, and its possible consequences for cerebral hemodynamics. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 110 publications
(38 reference statements)
0
46
0
1
Order By: Relevance
“…However, with respect to migraine aura, this traditional controversy between the vascular and neuronal theory dissolved when it became clear that epipial, i.e., abluminal, application of the vasoconstrictor polypeptide endothelin-1 is currently the most potent trigger of spreading depolarization in rodents in vivo and that endothelin-1 has this effect because of its vasoconstrictor properties, causing an imbalance between energy supply and demand of neurons (Dreier et al, 2002a). These findings have contributed significantly to the hypothesis that endothelial dysfunction could be one of the different etiologies leading to spreading depolarization and migraine aura in certain circumstances (Kleeberg et al, 2004;Dreier et al, 2007;Ducros, 2012;Dreier and Reiffurth, 2015;Liman et al, 2015;Oliveira-Ferreira et al, 2020;Paolucci et al, 2021). In recent clinical studies, intravenous infusion of endothelin-1 induced aura symptoms neither in healthy volunteers nor in patients with a history of migraine aura (Hougaard et al, 2020a,b).…”
Section: Introductionmentioning
confidence: 99%
“…However, with respect to migraine aura, this traditional controversy between the vascular and neuronal theory dissolved when it became clear that epipial, i.e., abluminal, application of the vasoconstrictor polypeptide endothelin-1 is currently the most potent trigger of spreading depolarization in rodents in vivo and that endothelin-1 has this effect because of its vasoconstrictor properties, causing an imbalance between energy supply and demand of neurons (Dreier et al, 2002a). These findings have contributed significantly to the hypothesis that endothelial dysfunction could be one of the different etiologies leading to spreading depolarization and migraine aura in certain circumstances (Kleeberg et al, 2004;Dreier et al, 2007;Ducros, 2012;Dreier and Reiffurth, 2015;Liman et al, 2015;Oliveira-Ferreira et al, 2020;Paolucci et al, 2021). In recent clinical studies, intravenous infusion of endothelin-1 induced aura symptoms neither in healthy volunteers nor in patients with a history of migraine aura (Hougaard et al, 2020a,b).…”
Section: Introductionmentioning
confidence: 99%
“…Although it is unclear whether caffeine is beneficial to systemic endothelial function, cerebral endothelial function, particularly CVR, differs from systemic endothelial function, at least in patients with migraine 18 . Cerebral circulation is different from systemic circulation as it is under complex control of neural, chemical, myogenic, and autonomic factors 22,24,30,41 . Caffeine can affect cerebral circulation through neural, chemical, and autonomic pathways as it is a neurostimulant as well as an adenosine receptor antagonist, and it can increase sympathetic nervous activity 42 .…”
Section: Discussionmentioning
confidence: 99%
“…We did not collect data regarding test reliability, but previous studies showed acceptable within‐day reliability of TCD BHI 29 . Based on previous studies, we selected MCA and PCA to represent anterior and posterior cerebral circulation 21,22 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been previously shown that endothelial dysfunction is common among patients with MPD, especially with thrombotic events [ 23 , 24 ]. FMD is a functional way to assess NO-mediated endothelial function; it involves measuring brachial artery dilation following a transient (≈5 min) period of forearm ischemia [ 25 ]. Lower FMD values are associated with endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 99%